Use of computed tomography in diagnosis and management of type III dens invaginatus - Jayshree Hegde; Kusum Bashetty; C Champa (Wolters Kluwer Medknow Publications, 2009)
Background: Dens invaginatus is a developmental malformation, which concerns the non-typical arrangement of dental hard tissues. Conventional diagnostic aids like radiographs play an important role in assessment of complex root canal morphologies. These modalities, however, do not provide detailed information of the complexity as a result of their inherent limitations. This calls for use of more advanced imaging modalities such as computed tomography, which can help the clinician in making a more accurate diagnosis. Report: Type III Dens invaginatus was detected in a 20 year old male patient corresponding to the maxillary lateral incisor and showing extensive periradicular radiolucency and a vestibular sinus. The radiographic and tomographic examination revealed 2 apices: one wide open in the distal part of the root and the other normally formed in the mesial. Treatment plan: Combined non-surgical and surgical endodontic therapy with MTA as a retrograde filling material was planned in this case. Outcome: At follow-up examination after 6 months, the tooth was asymptomatic and radiographically showed repair of the lesion.